2019
DOI: 10.3390/ijerph16193664
|View full text |Cite
|
Sign up to set email alerts
|

And in the Middle of My Chaos There Was You?—Dog Companionship and Its Impact on the Assessment of Stressful Situations

Abstract: Recent studies show evidence that human-dog companionship has healthy effects on humans. For example, findings demonstrate that owning a dog leads to a reduction in stress levels. Aspects that have not been taken into consideration so far are underlying theoretical principles of stress like the sense of coherence (SOC) by Aaron Antonovsky. The SOC consists of psycho-social, biochemical and physical conditions which indicate whether or not inner and outer stimuli are comprehensive, manageable and meaningful to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…It has been suggested that companion animals enhance SOC levels through enabling positive bonding experiences. To our knowledge, there is only one study investigating the relationship between dog ownership, SOC, and subjective evaluation of critical life events, which found-contrary to expectations-no differences in SOC levels between dog owners and others [39].…”
Section: Introductioncontrasting
confidence: 72%
See 1 more Smart Citation
“…It has been suggested that companion animals enhance SOC levels through enabling positive bonding experiences. To our knowledge, there is only one study investigating the relationship between dog ownership, SOC, and subjective evaluation of critical life events, which found-contrary to expectations-no differences in SOC levels between dog owners and others [39].…”
Section: Introductioncontrasting
confidence: 72%
“…We expected dog ownership to be associated with higher levels of health-benefitting factors because pet ownership has been associated with stronger social support and better emotion regulation strategies. However, up to date research on health-benefitting factors was scarce and the only study investigating the relationship between SOC and pet ownership did not find a significant association [39]. Moreover, the only study that assessed the relationship between LOC and pet ownership was conducted in individuals with physical disabilities, who showed an enhanced internal LOC six month after service dog adoption [47].…”
Section: Discussionmentioning
confidence: 99%
“…While studies in support of animal contact receive media attention, a very large longitudinal cancer study showed a shorter survival time compared to non-owners, especially for female cat or bird owners [18]. Another example is the media often touts dogs as relieving stress but one study found the impact is somewhat exaggerated [19]. Also, while there was never extensive research money, there was more funding for animal-assisted therapy (AAT) than for general animal studies of basic science value.…”
Section: The Need For Research and Evidence: Connecting The Dots Fmentioning
confidence: 99%
“…These will allow better responses to extreme heat events, reducing HRI severity and fatality [ 2 ]. Domestic dogs play important roles in society, including companionship [ 4 ] and fulfilling service roles ranging from military and policing to medical assistance. Climate change mitigation strategies must therefore include consideration of canine-specific risk factors to reduce HRI risk and severity in dogs and maintain the unique positions of dogs in human society [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%